2015
DOI: 10.4274/tjo.70456
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmomyiasis Externa: A Report of Three Cases

Abstract: Three patients were admitted to our clinic with symptoms of conjunctivitis. On ocular examination, moving larvae were seen in the conjunctival sac. All of the larvae were immobilized by topical cyclopentolate and removed mechanically under topical anesthesia. The patients healed without any complications after the treatment. Physicians should consider ophthalmomyiasis externa in patients presenting with similar symptoms, especially in areas with high numbers of livestock. Otherwise the diagnosis can be missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In the past decade, there have been reported cases of this infection in countries where autochthonous cases were previously unknown, such as the Czech Republic [46], Bulgaria [47], Australia [48], China [49], Serbia [19], Jamaica [50], South Africa [51], Morocco [52], Japan [53], Indonesia [54], Canada [55], Barbados [56], Belgium [57], Iraq [58], United Kingdom [59], Honduras [60], and Bolivia [61]. Despite its global prevalence [10,18], most reported cases are still concentrated in India [2,27,29,37,[62][63][64][65][66][67], Turkey [25,28,43,[68][69][70][71][72][73][74], Iran [20,40,75], and Libya [18,76].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the past decade, there have been reported cases of this infection in countries where autochthonous cases were previously unknown, such as the Czech Republic [46], Bulgaria [47], Australia [48], China [49], Serbia [19], Jamaica [50], South Africa [51], Morocco [52], Japan [53], Indonesia [54], Canada [55], Barbados [56], Belgium [57], Iraq [58], United Kingdom [59], Honduras [60], and Bolivia [61]. Despite its global prevalence [10,18], most reported cases are still concentrated in India [2,27,29,37,[62][63][64][65][66][67], Turkey [25,28,43,[68][69][70][71][72][73][74], Iran [20,40,75], and Libya [18,76].…”
Section: Discussionmentioning
confidence: 99%
“…Turkey ranks third in the world in the number of reported cases. Various studies have reported case numbers ranging from one to twelve [25,26,29,43,[68][69][70][71][72][73][89][90][91][92], with the causative agent predominantly being O. ovis and C. bezziana in only one case [89]. Interestingly, cases have occurred more frequently in urban areas without known animal contact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Irrigation of ocular surface is usually insufficient because larvae can attach the mucosa firmly with their hooks (7). Prior application of topical cyclopentolate or topical ivermectin is reported to immobilize or kill larvae and facilitate their mechanical removal (10,11). Anti-inflammatory drugs are prescribed to control host reaction and antibiotics against secondary infections.…”
Section: Discussionmentioning
confidence: 99%